LEGAL PROTECTION OF CONSUMERS IN INSURANCE AGREEMENTS GENERALLY AND ESPECIALLY MARINE HULL INSURANCE AS ONE OF INDONESIA'S ECONOMIC DEVELOPMENT - Marihot Simanjuntak; Tumanggor Tumanggor; Bernard Nainggolan; Wiwik Sri Widiarty (International Journal of Artificial Intelligence Research, 2022)
This study aims to determine consumer legal protection in general insurance agreements and special marine creep insurance as one of Indonesia's economic development. This research is a mixed research method (mix method), namely normative juridical and empirical juridical. Data collection techniques Primary, secondary, and tertiary legal sources are among the legal materials studied and evaluated in this normative legal study. The results of the study show that legal protection for consumers in insurance agreements and practices is generally regulated in the Civil Code, the Commercial Code, Law No. 40 of 2014 concerning Insurance Business and the Consumer Protection Act which each of these rules contains related to the legal protection of insurance agreements. Legal protection for insurance customers, the insurance (guarantor) will provide compensation to the insured (customer) in accordance with the methods and conditions contained in the policy. Against losses resulting from guaranteed risks such as property losses resulting from a hazard or disaster.